IT Multisourcing Management : A Qualitative Study from the Vendor's Perspective - Schmidt, Katharina (My University, 2018)
IT multisourcing is an outsourcing method that combines services of various different vendors in a single technology focused undertaking. This study investigates the benefits and disadvantages that an IT multisourcing setting presents to the vendor from a management perspective. As vendors are responding to client needs, studying their experiences can present valuable information for managing IT multisourcing projects for client companies and their decision makers. The study aims to gather as much information of multisourcing from the vendors’ perspective, but due to the main focus in previously conducted research articles being on the client’s side, there is a gap in research to be filled. This study aims to fill the gap by interviewing eight IT industry experts with experience from IT outsourcing and multisourcing projects. As multisourcing describes a situation where one client contracts two or more independent vendors on a single IT project or undertaking, it is also a situation where the different tasks assigned to vendors have some impact on each other. This is true in most cases, even though the vendors may operate independently from each other. It has been shown that multisourcing is only efficient when vendors are communicating with each other. This study also focuses on examining the communication and cooperation activities of the various operators in a multisourcing setting. Through examination of a selection of most ocmmonly used models in IT multisourcing, the thesis aims to expand the knowledge on what the benefits and disadvantages of IT multisourcing are as well as what the management challenges in these settings are with an emphasis on the vendor's view point.
Keywords: IT Multisourcing, multisourcing, multi-sourcing, multisourcing management, outsourcing